Photocatalytic hydrogen evolution assisted by aqueous (waste)biomass under simulated solar light: Oxidized g-C3N4 vs. P25 titanium dioxide. (8th February 2019) - Speltini, Andrea; Gualco, Francesca; Maraschi, Federica; Sturini, Michela; Dondi, Daniele; Malavasi, Lorenzo; Profumo, Antonella
Abstract: Oxidized graphitic carbon nitride (o-g-C3 N4 ) and Evonik AEROXIDE ® P25 TiO2 were compared for lab-scale photocatalytic H2 evolution from aqueous sacrificial biomass-derivatives, under simulated solar light. Experiments in aqueous starch using Pt or Cu–Ni as the co-catalysts indicated that H2 production is affected by co-catalyst type and loading, with the greatest hydrogen evolution rates (HER) up to 453 and 806 μmol g −1 h −1 using TiO2 coupled with 3 wt% Cu–Ni or 0.5 wt% Pt, respectively. Despite the lower surface area, o-g-C3 N4 gave HERs up to 168 and 593 μmol g −1 h −1 coupled with 3 wt% Cu–Ni or 3 wt% Pt. From mono- and di-saccharide solutions, H2 evolution was in the range 504–1170 μmol g −1 h −1 for Pt/TiO2 and 339–912 μmol g −1 h −1 for Cu–Ni/TiO2, respectively; o-g-C3 N4 was efficient as well, providing HERs of 90–610 μmol g −1 h −1 . The semiconductors were tested in sugar-rich wastewaters obtaining HERs up to 286 μmol g −1 h −1 . Although HERs were lower compared to Pt/TiO2, a cheap, eco-friendly and non-nanometric catalyst such as o-g-C3 N4, coupled to non-noble metals, provided a more sustainable H2 evolution. Graphical abstract: Highlights: o-g-C3 N4 is compared to P25 TiO2 for H2 photoevolution from aqueous saccharides. o-g-C3 N4 provides H2 from starch solution up to 75% compared to P25 TiO2 . Cu–Ni co-catalysts afford H2 up to 56% (TiO2 ) and 30% (o-g-C3 N4 ) compared to Pt. H2 evolution from food factories wastewaters under simulated solar light is tested. The potential applicability of o-g-C3 N4 for clean H2 photogeneration is shown.